Great Expectations: Principal Investigator and Trainee Perspectives on Hiring, Supervision, and Mentoring. Issue 9 (7th September 2018) - Kaps, Leonard; Stine, Jonathan G.; Mellinger, Jessica; Vilarinho, Silvia
Abstract : A functioning mentor–trainee relationship is of high importance in academia. Discrepancies in expectations between principal investigators (PIs) and trainees are a source of misunderstandings and conflicts, endangering scientific progress and career advancement. In this pilot study, we sought to explore the expectations of PIs and trainees, providing consensus data from physician‐scientists and junior researchers who attended an educational workshop, entitled "The EASL/AASLD Masterclass, " in December 2017. Twenty‐three Masterclass attendees, comprising nine trainees (four Ph.D. candidates, five postdoctoral researchers) and 14 PIs, responded to an online survey. Both parties were asked to score 29 predefined statements of important expectations, enabling a comparative analysis for each statement between the groups. For the trainees, the success of the PI, either mirrored by successful mentoring or scientific work, as well as a clear road for academic development are of utmost importance. PIs did not prioritize these aspects, highlighting discrepancies of expectations. PIs prioritized trainee competence, reliability, and strong daily initiative/work ethic, qualities that were also recognized to be important by the trainee group but not to same degree as PIs. Conclusion :Discrepancies in expectations pose a preventable threat to the mentor–trainee relationship if considered and discussed beforehand. The discrepancy in the most common expectations between the two groups could have resulted from the fact that trainees prioritize outcomes of success while PIs focus on the necessary qualities leading to those outcomes.